Tonal language background and detecting pitch contour in spoken and musical items. (January 2013) - Stevens, Catherine J.; Keller, Peter E.; Tyler, Michael D.
An experiment investigated the effect of tonal language background on discrimination of pitch contour in short spoken and musical items. It was hypothesized that extensive exposure to a tonal language attunes perception of pitch contour. Accuracy and reaction times of adult participants from tonal (Thai) and non-tonal (Australian English) language backgrounds were recorded as they discriminated intact and low-pass filtered Thai and English items that differed in rising/falling contour (speech task), and musical items that differed in rising/falling contour, major/minor interval, and contour plus interval features (music task). As hypothesized, the tonal language group was significantly faster and more accurate at discriminating intact speech items on the basis of pitch contour. The tonal language group was also significantly faster in response to musical contour and intervals, although accuracy was equivalent across language groups. The results provide some support for the contention that a tonal language environment fosters perceptual attunement to contour in spoken items and this can generalize to relatively fast responding to contour in a more musical setting.